Morphology of Drained Upland Depressions on the Des Moines Lobe of Iowa - McDeid, Samuel M.; Green, David I. S.; Crumpton, William G. (Wetlands (Wilmington, N.C.), 2019)
An algorithm developed to derive the morphology of depressional landscape features was applied to the Iowa portion of the Des Moines Lobe using high-resolution hydrologically corrected digital elevation models. In total, 173,171 topographically intact, drained upland depressions were identified, and their individual morphologies determined. The frequency distributions of maximum area of inundation, maximum depth, and maximum storage volume of depressions were described by a power-law function. Maximum storage volume was strongly related to maximum inundation area through a power-law model, the parameters of which differ from those reported for other areas of the North American Prairie Pothole Region. The spatial distributions, densities, and bulk morphological attributes of upland depressions within the DML-IA tend to be coincident with the region's distinctive glaciated sub-regions.